The development of Vietnamese language supplementary courses in daily life for improvement of speaking ability using the 3ps approach to language teaching for grade 9 students - Wetchakama, Manutsawi; Tanunchaibutra, Prin (Journal for Developing the Social and Community, 2023)
The purposes of this research and development were 1) to develop the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students; 2) to develop the Vietnamese speaking ability of grade 9 students who were studied following the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students, and the students were required to have the average score not less than 70 percent and there were the amount of students who passed more than 70 percent of the criteria. The target group of this research was 22 students who were studying in grade 9, class 3/13, during 1st semester of academic year 2021 at Kalasin Pittayasan School, Amphoe Mueang Kalasin, Kalasin Province. This school is belonged to the secondary educational service area of Kalasin province, and the target group was chosen by purposive sampling. This research was research and development (R&D) which consisted of research instruments for collecting data were 1) a survey form of problem conditions and people’s needs in developing the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students; 2) an opinion interviewing form about the necessary importance and compositions in developing the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students; 3) the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students; 4) 4 lesson plans based on using the 3 Ps approach to language teaching for grade 9 students; 5) an evaluation test for Vietnam speaking ability. The data were analyzed in terms of mean (), standard deviation (S.D.), and percentage (%). The findings of the study were as follows: 1) The result of an evaluation form of capacity in the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students by experts who checked the research instruments, was found that the capacity was at a high level, there had got overall mean () at 4.47 and standard deviation (S.D.) at 0.46. This demonstrated that the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students (draft) was capability for trying out. 2) The result of an evaluation test the Vietnamese speaking ability of grade 9 students who were taught followed by the development of Vietnamese Language program in daily life for improvement of speaking ability using the 3 Ps approach to language teaching for grade 9 students, was found that overall mean () of the evaluation test for English critical reading competence was at 17.36 and its percentage was at 85. Then there had 22 students who passed the criteria and their percentage was at 100, which was higher than determined criteria.